(untitled) (Interdisciplinary Studies Journal, 2025)
This study aims to explore the impacts of artificial intelligence (AI) on individual and collective rights, particularly within the Brazilian legal context. With the advancing tools of AI, especially in the judiciary, the question arises regarding the potential for AI to be used in automated judicial decision-making and the risks of violating fundamental rights guaranteed by the 1988 Constitution and related legislation. Divided into three chapters, the research first addresses aspects of AI and its application, followed by an analysis of individual and collective rights. The third chapter examines how AI applications may affect these rights, emphasizing ethical concerns and the need to preserve human sensitivity and equitable justice. The methodology employed is qualitative, utilizing literature and document review, including relevant case law. The ultimate goal is to achieve a balance between technology use and the protection of democratic values and fundamental rights, essential for an inclusive and just society.